Integrated analysis of BSA-seq and RNA-seq identified the candidate genes for seed weight in Brassica juncea - Yang, Bin; Yang, Liu; Kang, Lei; You, Liang; Chen, Hao; Xiao, Huagui; Qian, Lunwen; Rao, Yong; Liu, Zhongsong (Frontiers in Plant Science, 2024)
Brassica juncea is a major oilseed crop of Brassica. The seed weight is one of yield components in oilseed Brassica crops. To map the genes for seed weight, the parental and F2 extreme bulks derived were constructed from the cross between the heavy-seeded accession 7981 and the light-seeded one Sichuan yellow (SY) of B. juncea, and used in bulk segregant sequencing (BSA-seq). A total of thirty five SNPs were identified in thirty two genes located on chromosomes A02 and A10, while fifty eight InDels in fifty one genes located on A01, A03, A05, A07, A09, A10, B01, B02 and B04. Meanwhile, RNA-sequencing (RNA-seq) was performed for both parents at six seed development stages. A total of 7,679 differentially expressed genes were identified in developing seeds between the parents. Furthermore, integrated analysis of BSA-seq and RNA-seq data revealed a cluster of nine genes on chromosome A10 and one gene on chromosome A05 that are putative candidate genes controlling seed weight in B. juncea. This provides a foundation for research on seed weight in Brassica species.